2019
DOI: 10.1557/jmr.2018.466
|View full text |Cite
|
Sign up to set email alerts
|

A green steam-modified delignification method to prepare low-lignin delignified wood for thick, large highly transparent wood composites

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…As shown in Figure 1e, Raman spectra revealed that peak intensity of B-wood at 1300, 1602, and 1730 cm −1 decreased compared with that of N-wood, which further demonstrated the removal of most of the lignin in B-wood [37]. Moreover, the degradation of the cellulose was negligible, while both lignin and hemicellulose were dramatically removed, as shown in our previous work [38]. The color changed from yellow to white during delignification process, shown in Figure 1f.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As shown in Figure 1e, Raman spectra revealed that peak intensity of B-wood at 1300, 1602, and 1730 cm −1 decreased compared with that of N-wood, which further demonstrated the removal of most of the lignin in B-wood [37]. Moreover, the degradation of the cellulose was negligible, while both lignin and hemicellulose were dramatically removed, as shown in our previous work [38]. The color changed from yellow to white during delignification process, shown in Figure 1f.…”
Section: Resultssupporting
confidence: 76%
“…Natural basswood (N-wood) slices with size of π × 20 × 20 × 5 mm 3 were obtained by cutting along the direction perpendicular to the growth of wood. Half-B-wood and B-wood were obtained by H2O2 steam delignification of above-mentioned N-wood at 100 C for 1 and 4 h, respectively [38]. After rinsed with water, and ethanol for three times, they were dried at 50 C for 4 h. The photodegradation process of BP-wood consists of the following steps.…”
Section: Preparation Of N-wood and B-woodmentioning
confidence: 99%
“…2 It was observed that surface modification 1 and lamination 8 of delignified wood template lamellae can be used to tune light scattering/haze and also transmittance. Previous work focused mostly on either total transmittance at particular TW thicknesses, 2,10 or angular distribution of light transmitted through TW at various thicknesses. 19 A quantitative relationship between total transmittance and sample thickness, however, is rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The lignin component in biomass can be removed through cooking/bleaching in NaOH/Na 2 SO 3 [53], NaClO 2 / glacial acetic acid [54], or H 2 O 2 /(acetic acid) steam [55]. Generally, the degree of delignification can be controlled by the processing time and temperature [56].…”
Section: Preparation Of Macroscopic Cellulose Productsmentioning
confidence: 99%